2022
DOI: 10.3390/jpm12101542
|View full text |Cite
|
Sign up to set email alerts
|

Personalized Communication with Patients at the Emergency Department—An Experimental Design Study

Abstract: Communication of clinicians at the emergency department is a barrier to patient satisfaction due to lack of human connection, lack of control over the situation, low health literacy, deficient information, poor support at a time of uncertainty all affecting perceived quality of care. This explorative study tests drivers of patient satisfaction with communication of clinicians at the emergency department. The sample comprises 112 Americans from the New York greater area, who visited an emergency department in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…Thus, offerings of communication in telemedicine should not be tailored to different demographic groups but rather to mindsets. These findings echo previous studies that suggested that patients should be segmented by their expectations from clinicians based on their mindset-belonging description rather than on demographics, driving patient satisfaction and health behaviors and enabling clinicians to use mindset-tailored communication to meet patient expectations and enhance the quality of care [57][58][59][62][63][64].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Thus, offerings of communication in telemedicine should not be tailored to different demographic groups but rather to mindsets. These findings echo previous studies that suggested that patients should be segmented by their expectations from clinicians based on their mindset-belonging description rather than on demographics, driving patient satisfaction and health behaviors and enabling clinicians to use mindset-tailored communication to meet patient expectations and enhance the quality of care [57][58][59][62][63][64].…”
Section: Discussionsupporting
confidence: 80%
“…The strongest messages for this mindset were "The clinician walks me through a change process to maintain my health" (beta = 12); "The clinician talks to me about my expectations" (beta = 12); and "The clinician helps me take responsibility for my health" (beta = 9). They expect clinicians to use messages that empower and navigate them to better manage their illness leading to higher resilience [57][58][59]. Members of mindset 3, comprising 31% of the sample, have an external locus of control and strongly oppose a change process guided by the clinician to maintain their health (beta = −12), to help them take responsibility for their health (beta = −13), or dialogue about their communication expectations (beta = −14).…”
Section: Secondary Analysismentioning
confidence: 99%
“…This particular discovery underscores the exigency for campaigns that heighten awareness, elucidating AF’s potential ramifications among individuals devoid of pre-existing health conditions. The broad spectrum of attitudes, encompassing concerns regarding AF-related complications on one end and apathy or skepticism on the other, underscores the pivotal role of communication strategies ( 23 , 24 ). Clinicians can harness this comprehension to formulate patient-centric narratives, tailored to resonate with diverse dispositions, thereby fostering heightened engagement and empowerment.…”
Section: Discussionmentioning
confidence: 99%